2012
DOI: 10.1111/j.1529-8019.2012.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Ungual melanoma - controversies in diagnosis and treatment

Abstract: Ungual melanomas are considered rare, being difficult to diagnose, and having a poor prognosis. The aim of the present study was to discuss the epidemiology, potential causes, treatment options, and outcome of ungual melanomas. In contrast to assumptions in many articles, ungual melanomas are not rare when calculated for the cumulative size of the nail apparatus of both the fingers and toes. The prognosis is not worse than that of melanomas with the same thickness, mitotic rate, or presence of ulceration on ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 75 publications
1
72
0
9
Order By: Relevance
“…NAM is more frequent between the ages of 50 and 70 years [1], but in rare occasions can also be observed in children [24,25]. More than half of the subjects were younger than 50 years, including an 8-year-old child.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NAM is more frequent between the ages of 50 and 70 years [1], but in rare occasions can also be observed in children [24,25]. More than half of the subjects were younger than 50 years, including an 8-year-old child.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is unclear about which gender is more affected [1]. In Japan, Korea, and Taiwan, there is a male predominance [16][17][18], whereas a female predominance is observed in Western countries [6,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative studies of various amputation levels have not shown any advantages for metacarpal amputations over metacarpophalangeal (MP), proximal interphalangeal (PIP), or distal interphalangeal (DIP) amputations [30]; this means that the prognosis of SUM does not depend on the amputation level but on the clinical stage [31]. Therefore, the recent trend of surgery is to utilize more distal amputations, without compromising recurrence or survival [25,26].…”
Section: Invasive Summentioning
confidence: 99%